Pembuatan Game Edukasi Pengenalan Alat Musik Tradisional Kalimantan Timur Berbasis Android - Ibra Ariyana; Yusni Nyura; Anton Topadang (JURNAL VOKASI TEKNIK, 2025)
East Kalimantan is famous for its rich culture, one of which is traditional musical instruments for example Sape, Kelentangan, and Gambus. These musical instruments have deep cultural and historical value, but interest in them is declining due to a lack of introduction and socialization to the next generation. Therefore, the author conducted research with the aim of creating an Android-based educational game for East Kalimantan traditional musical instruments, so that it can be used as a learning medium for elementary school students so they can recognize and understand the musical instruments found in East Kalimantan. This educational game introduces 3 types of traditional East Kalimantan musical instruments, namely Sape, Kelentangan, and Gambus. This game consists of material on introducing musical instruments, playing musical instruments, puzzle games and quizzes. Making games using Construct 2 and the ADDIE Development Model (Analysis, Design, Development, Implementation, Evaluation). Construct 2 is used in this research because Construct 2 is one of the games that is popular with game developers and is easy to use, while the ADDIE development model is used because the framework is simple and easy to use for creating various types of media. Furthermore, this research has produced an educational game introducing traditional East Kalimantan musical instruments based on Android and can be used as a learning medium for elementary school students, based on the results of material validation and media validation experts.